La rencontre entre les délinquants et les pédés [1961] - Albert J. Reiss (Genre, Sexualité et Société)
This paper explores a special form of male prostitution in American society, a homosexual relationship between adult male fellators and delinquents. It is seen as a financial transaction between boys and fellators which is governed by delinquent peer norms. These norms integrate the two types of deviators into an institutionalized form of prostitution and protect the boys from self-definitions either as prostitutes or as homosexuals. The conclusions offered in this paper must be regarded as tentative, because of limitations inherent in the data. Study of the fellator population might substantially change the conclusions. Cross-cultural studies also are necessary. Discussion of these findings with criminologists in Denmark and Sweden and exploratory investigations in several larger American cities, however, suggest that the description and explanation offered in this paper will hold for other American cities and for some other social systems.